Data warehousing and knowledge discovery : Second International Conference, DaWak 2000, London, UK, September 4-6, 2000 : proceedings - Kambayashi, Y.; Mohania, Mukesh; Tjoa, A Min (Lecture notes in computer science, 2000)
This book constitutes the refereed proceedings of the Second International Conference on Data Warehousing and Knowledge Discovery, DaWaK 2000, held in London, UK in September 2000. The 31 revised full papers presented together with 11 short papers were carefully reviewed and selected from a total of more than 90 submissions. The papers are organized in topical sections on data warehouse design, materialized views, warehouse data creation and maintenance, warehouse views selection and evolution, OLAP system design and query association rules, temporal association rules, and mining complex databases.